Aluminum and Aluminum Alloys Systematic mapping on different Aluminum and Aluminum Alloys practices and benefits and outcome performance by Weka application: Systematic mapping on different Aluminum and Aluminum Alloys practices and benefits and outcome performance by Weka application - mohamed, ali; Darmeesh , Adel Khalleefah Hamad (International journal of technology and education research, 2023)
Abstract Aluminum is one of the most adaptable, cost-effective, and visually appealing metallic materials available for a variety of applications, from soft, highly ductile wrapping foil to the most rigorous engineering ones. Furthermore, this is due to the special combinations of properties that aluminum as well as its alloys offer. Moreover, the only other metal used as a structural material after steel is aluminum alloys. Just 2.7 g/cm3 is what aluminum is made of about a third as much as steel (7.83 g/cm3). Aluminum weighs just around 170 lb per cubic foot, compared to approximately 490 lb for one cubic foot of steel. In a similar manner, coupled with the high strength of some aluminum alloys (exceeding that of structural steel), permits design as well as construction of strong, lightweight structures that are especially advantageous for anything that moves space vehicles also, aircraft as well as all types of land- as well as water-borne vehicles. Aluminum is resistant to the type of gradual oxidation that makes steel rust. An inert aluminum oxide coating, barely a few ten-millionths of an inch thick, is created when oxygen reacts with the exposed aluminum surface to prevent further oxidation. Moreover, unlike iron rust, the aluminum oxide coating does not flake off to reveal a new surface to oxidation. Immediately after being scratched, the aluminum's protective covering will close back up. The metal is strongly adhered to a thin layer of colorless, transparent oxide that is undetectable to the naked eye as well as adheres to the metal tightly. Aluminum does not rust, which results in the discoloration also, flaking that happens to iron as well as steel. Aluminum can withstand corrosion from a variety of chemical and physical agents as well as from water, salt, and other environmental variables when alloyed as well as handled properly. The section